The Impact Of The United States Foreign Policy During The Donald Trump Government On Global Climate Governance - Dwi Ardyanti; Darmelia Puspita Sari (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
The problem of climate change is one of the most crucial issues today. The various impacts that have occurred due to climate change have increased the world community's awareness of the effects in the future. This was exacerbated by the existence of U.S. foreign policy when the Trump administration voted to exit the Paris Agreement. The lack of research into the impact of the U.S withdrawal from the Paris Agreement on tackling global climate issues has prompted the study. This paper will analyze the impact of what has arisen from the U.S withdrawal from the Paris Agreement during the Trump administration, using foreign policy theory in interpreting the actions or policies taken by Donald Trump in the withdrawal from the Paris Agreement, the constructivist approach used in analyzing international regime formation as a social construct, the concept of climate governance in analyzing the impacts that occur, and the Theory of International Regimes initiated by Stephen Krasner examines the world's climate change regime. The method used in this research is a qualitative research method with explanative writing techniques. This study shows that there are three significant impacts resulting from the Withdrawal of the United States from the Paris Agreement, among others, the increase in global emissions that are bad for the environment, which is indicated by increased activity that produces gas emissions in the United States region. Second is the decline of climate finance mechanisms that will affect the quality of climate change reports produced. Third, this withdrawal will also affect global climate governance, which will affect the compliance of member countries to the agreement.